Cognitive flexibility and performance in children and adolescents with threshold and sub-threshold bipolar disorder. - Dickstein, Daniel; Axelson, David; Weissman, Alexandra; Yen, Shirley; Hunt, Jeffrey; Goldstein, Benjamin; Goldstein, Tina; Liao, Fangzi; Gill, Mary; Hower, Heather; Frazier, Thomas; Diler, Rasim; et al. (European Child & Adolescent Psychiatry, 2016)
Greater understanding of cognitive function in children and adolescents with bipolar disorder (BD) is of critical importance to improve our ability to design targeted treatments to help with real-world impairment, including academic performance. We sought to evaluate cognitive performance among children with either BD type I, II, or 'not otherwise specified' (NOS) participating in multi-site Course and Outcome of Bipolar Youth study compared to typically developing controls (TDC) without psychopathology. In particular, we sought to test the hypothesis that BD-I and BD-II youths with full threshold episodes of mania or hypomania would have cognitive deficits, including in reversal learning, vs. those BD-NOS participants with sub-threshold episodes and TDCs. N = 175 participants (BD-I = 81, BD-II = 11, BD-NOS = 28, TDC = 55) completed Cambridge Neuropsychological Automated Testing Battery (CANTAB) tasks. A priori analyses of the simple reversal stage of the CANTAB intra-/extra-dimensional shift task showed that aggregated BD-I/II participants required significantly more trials to complete the task than either BD-NOS participants with sub-syndromal manic/hypomanic symptoms or than TDCs. BD participants across sub-types had impairments in sustained attention and information processing for emotionally valenced words. Our results align with prior findings showing that BD-I/II youths with distinct episodes have specific alterations in reversal learning. More broadly, our study suggests that further work is necessary to see the interaction between neurocognitive performance and longitudinal illness course. Additional work is required to identify the neural underpinnings of these differences as targets for potential novel treatments, such as cognitive remediation.